Reassessment of FBN1 variants of uncertain significance using updated ClinGen guidance for PP1/BS4 and PP4 criteria - Ju Hyeon Shin; Young‐Gon Kim; Shin Yi Jang; June Huh; Duk‐Kyung Kim; Jong‐Won Kim; Ja‐Hyun Jang; Taek Kyu Park; Mi‐Ae Jang (2025)
Abstract Marfan syndrome (MFS) is a genetic disorder caused by an FBN1 variant and is diagnosed based on the revised Ghent criteria, which incorporate clinical manifestations and genetic testing. Up-to-date FBN1 variant interpretation is crucial for proper diagnosis and management of MFS; however, some FBN1 variants of uncertain significance (VUSs) remain inconclusive despite applying Clinical Genome Resource (ClinGen) FBN1 -specific guideline. Recently, the ClinGen guidance for PP1/BS4 co-segregation and PP4 phenotype specificity criteria (new PP1/PP4 criteria) were released. Here, we performed reassessment of FBN1 VUSs using these new PP1/PP4 criteria. FBN1 VUSs collected from December 2015 to April 2024 were reassessed according to the ClinGen FBN1 -specific guideline and new PP1/PP4 criteria. Medical records and previous studies were reviewed to evaluate the phenotype-specificity of evidence based on the revised Ghent criteria. Collectively, 927 patients with suspected MFS underwent FBN1 sequencing and 72 VUSs were detected. When applying the FBN1 -specific guideline only, of 72 VUSs, 29 (40.3%) were reclassified as pathogenic variants (PVs) or likely PVs (LPVs). When additionally applying the new PP1/PP4 criteria, 16 (37.2%) of the remaining 43 VUSs were reclassified as LPVs. After reassessing FBN1 VUSs according to the new PP1/PP4 criteria, the rate of reclassification from VUS to PV/LPV significantly increased from 40.3% to 62.5%. The new PP1/PP4 criteria provide sufficient evidence for evaluating the pathogenicity of FBN1 variants detected in MFS patients fulfilling the revised Ghent criteria and will be helpful in clinical analysis.